Influence of anoxemia on the hematopoietic activity - Hurtado, Alberto (1946)
Research has been conducted at sea level and at altitude, in several groups of subjects (male), healthy and sick, concerning the influence of chronic temporal anoxic anoxia (anoxemia), intermittent and, on the morphology and other features circulating blood. The related literature has been briefly reviewed.